GENDER MAINSTREAMING IN THE HERMENEUTICS OF ISLAMIC FAMILY LAW - Athoillah Islamy (Al-Bayyinah, 2020)
The problem of gender discrimination for women can occur in all spaces, both public and private spaces as well as in family life. This problem is not only caused by biased socio-cultural construction but can also be caused by biased interpretation of Islamic teachings. Even Though in the Qur'an and the Hadith itself highly upholds the equality of existence between men and women. There are two main objectives in this study. First, to find gender mainstreaming in the construction of Amina Wadud's al-Qur'an hermeneutic method. Second, to understand the application of Amina Wadud's hermeneutic method in interpreting verses about the pattern of gender relations in the family. This research is qualitative in the form of a literature study with a philosophical normative approach. The primary source used is an explanation of Amina Wadud's hermeneutic method in her book entitled Qur'an and Woman Rereading the Sacred Text from a Woman's Perspective. Meanwhile, secondary sources used are various relevant studies. There are two big conclusions of this research. First, Amina Wadud's hermeneutic al-Qur'an method considers three aspects as the basis for the interpretation of a text (verse), among others, the context in which the text was written and interpreted, the grammatical text, and the weltansanschaung. By considering these three aspects, Wadud tried to reinterpret a theological basis (verses of the Qur'an) related to the pattern of gender relations that have been interpreted by many classical commentators. Secondly, Wadud better understood the verses of gender relations in the family as functionalist relations. The functional relationship in question is the cooperative relationship over the distribution of rights and responsibilities between men and women based on their potential.Keywords: Hermeneutics; Amina Wadud; Gender Relations; Family.